Pidana Adat Baduy dalam Perspektif Pembaharuan Hukum Pidana Nasional - Yusman Yusman (Rechtsregel : Jurnal Ilmu Hukum, 2021)
The renewal of the National Criminal Law is a discourse that has long been held by the Indonesian people. The Criminal Code (KUHP) is considered no longer able to fully accommodate legal interests in the era of globalization. The Criminal Code is actually a memento from the colonial period, where the criminal code was adopted from the criminal law system of the Dutch colonial nation. One of the things discussed in the discourse and travel or criminal law reform process is the accommodation of customary law in the draft revision of the KUHP law (RUU KUHP). This research makes the Bedouin customs as the object of study. The selection of the Bedouin community itself is because the Bedouin has its own customary criminal code and is the closest indigenous tribe to the capital city. The Baduy are a strong indigenous tribe who defend their customs from the influence of modernization. Then on the existence of such facts, the question arises how is the existence of Bedouin customary law in the discussion of national criminal law reform, these questions will be answered in this study using qualitative methods that will produce descriptive data.